The reformist elites in the Arab Maghreb between the ideology of the Islamic league and the Arabic nationalism ideology - yazir, mohamed (Journal of Social Sciences and Humanities, 2021)
The idea of Islamic foundation appeared as an intellectual religions movement at the beginning of the 19th centry, that relates Islamic societies to rightions religion sowces,and forms a solid stronghold to wards foreigh threats that targeted othoman state, in the some time appeared the Arabic nationalism call through many both secret and overt associations headed by Christian arabs in the Arabic mashrek as a reaction of imposed turanisem policy by the etihad and taraqui association after its hold of power in the ottoman starte, and appearance of other nationalisms and the oppression against arabs in some Arabic regions, hence it was considered as an occupation. in the Arabic Maghreb (North Africa) the reformist elite did not make any difference between arabic nationalism and islam. Abdul-Aziz althaalibi in Tunisia called to Islamic fondation in the bigining of his political and intellectuallife,but after the 1st world war and the collapse of caliphate in 1924,he turned to Arabic nationalism. as for Abdelhamid benbadis who called to both arabic and islam according to his eternal statement « Arabic is our language ,islam is our religion, and Algeria is our contry ».